2021
DOI: 10.24042/ijsme.v4i3.7689
|View full text |Cite
|
Sign up to set email alerts
|

Creative Problem Solving-Based Electronic Module Integrated with 21st Century Skills

Abstract: Teachers as facilitators in learning are expected to develop learning that integrates 21st-century skills so that students are ready to compete in this era. One of the things teachers can do is develop e-modules based on the Creative Problem Solving (CPS) model. This research is research and development with 4D models. The purpose of this study is to produce an integrated 21st-century physics e-module based on the CPS model. Data analysis using descriptive analysis. Research results: E-module physics based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…dynamically to produce a more complete understanding. Several other studies have also suggested the importance of developing teaching materials in an interactive form to better support conceptual understanding and some higher order thinking skills [29]- [31], especially if to learn microscopic concepts, the use of visual multimedia is highly recommended to be able to increase the level of understanding of concepts towards scientific concepts [32]- [34].…”
Section: Resultsmentioning
confidence: 99%
“…dynamically to produce a more complete understanding. Several other studies have also suggested the importance of developing teaching materials in an interactive form to better support conceptual understanding and some higher order thinking skills [29]- [31], especially if to learn microscopic concepts, the use of visual multimedia is highly recommended to be able to increase the level of understanding of concepts towards scientific concepts [32]- [34].…”
Section: Resultsmentioning
confidence: 99%
“…The STEM approach is often used to solve problems in everyday life. Through the STEM approach, the learning process will go through the application and primary practice of STEM in real life by connecting the four components of STEM [27]. STEM integration in learning is expected to increase the skills needed in the 21st century: student problem-solving, innovation, invention, independence, logical thinking, and technological literacy skills [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ashari & Salwah (2017), also explained that problem-based e-modules have problems that will be investigated and solved so that they can train students' problem-solving abilities. Learning that uses problem-based e-modules encourages students to think critically, increases creativity in solving problems, and students are able to collaborate to solve problems and communicate solutions between friends (Widya et al, 2023). Based on the explanation above, the aim of this research is to develop a PBL-based Lichens diversity emodule to improve students' problem-solving skills.…”
Section: Introductionmentioning
confidence: 99%